If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -8 = 70 Reorder the terms: -8 + 12x = 70 Solving -8 + 12x = 70 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 12x = 70 + 8 Combine like terms: -8 + 8 = 0 0 + 12x = 70 + 8 12x = 70 + 8 Combine like terms: 70 + 8 = 78 12x = 78 Divide each side by '12'. x = 6.5 Simplifying x = 6.5
| (-3)*(-3)*(-3)*(-3)+x=10x | | 109-9v=19 | | 15x^3+11x^2-14x=0 | | 13=117-8w | | 81+x=10x | | v/7-2=1 | | 22-2k=14 | | 5.4=-logx | | -6(2-3x)-3=-15+2x | | (-3)*(-3)*(-3)+x=10x | | p/4-1=3 | | 4.7x+3.8=13.2l | | -2v+5v=-12 | | 445.53=.71x | | d/3-6=-2 | | X/8=21/14 | | x/4-9=-11 | | 5n-5=5n+10 | | 2/5*25=10 | | 4x+6y=4200 | | -11x=17 | | 2x-66=12 | | 7d+3=94 | | -9=-2v+5 | | 1/3xyz=p | | h/4-6=-1 | | 22-5p=57 | | q/8-1=2 | | 8x+4=92 | | 4x-6-2x=4 | | Q-1/21/2 | | -5+2m=25 |